INTERPRETASI KENABIAN(Peran Ganda Nabi Muhammad Sebagai Manusia Biasa dan Rasul) - Wardi, Moh. (Universitas Islam Madura, 2015)
Prophet Muhammad represents one figure of many world figures, but in the middle age of its action as human being it did not miss from various human being characters like forgetting and doing wrongness to others. He did not only undertake to become Messenger, but also as leader of State and as person. Prophet‟s word was as his products must be selected carefully. There must be determination, which was outside of his capacities as Messenger That way we do not be trapped by stiff teaching. Knowledge from Him as prophet can give the understanding about Ulumul Hadist. Thereby we know how far the scope of Prophet‟s words, going into public pass history quickly, Without deep knowledge, secretary of Hadist did not do an interpretation so that we will not fall to in wrong conclusion, narrow, tight and stiff teaching because we are unable to differentiate dimension of Uluhiyyah and dimension of history.